Determination of Sea Ice Freeboard in Arctic from ICESat: Case Study of 2005—2006 - CHEN Guodong; LI Jiancheng; CHU Yonghai; LI Dawei (Surveying and Mapping Press, 2015)
Based on variation characters of sea surface height and parameters of ICESat return pulse waveform, a method is proposed for estimating Arctic sea ice freeboard with ICESat observation. This proposed method is compared with the common ‘lowest-level’ method. The results show that the lowest-level method is vulnerable to gross errors and present systematic errors in spatial distribution of freeboard. But the proposed method is more reliable than the lowest-level method. The lowest-level method is improved by the employ of an elevation standard deviation threshold and combined with the proposed method to estimate sea ice freeboard for six ICESat campaigns between 2005 and 2006 to review the seasonal variability. The results show that the abnormal climate in the summer of 2005 have a profound impact on arctic sea ice, which caused the decrease of freeboard and changed the constituent of sea ice as well.